INOVASI DAN URGENSINYA DALAM DUNIA PENDIDIKAN ISLAM - Atnawi, Atnawi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
Educational innovation aims to solve educational problems and function as novelties for a person or group (community), in an effort to achieve educational goals. In the context of Islamic education, Innovation will produce a positive thing if the practitioners of Islamic education understand some of the concepts and characteristics of Islamic education innovation. So the educational innovation models can be grouped into: 1) Invention (Invention), 2) Development (Development), 3) Diffusion (Spreading). While the characteristics of educational innovation include 1) Relative advantage, 2) Compatibility, 3) Testability, 4) Observability, 5) Complexity, Characteristics are obtained from concept maps: a) Reatif advantages, benefits, user benefits, economical, user satisfaction, b) Complexity, complexity, difficulty level, c) Compatibility, conformity with value, conformity with experience, suitability, d) Trialability, testable, moving and fact. E) Observability and so on